2022
DOI: 10.1186/s12935-022-02523-z
|View full text |Cite
|
Sign up to set email alerts
|

MUC1 is a potential target to overcome trastuzumab resistance in breast cancer therapy

Abstract: Although resistance is its major obstacle in cancer therapy, trastuzumab is the most successful agent in treating epidermal growth factor receptor 2 positive (HER2 +) breast cancer (BC). Some patients show resistance to trastuzumab, and scientists want to circumvent this problem. This review elaborately discusses possible resistance mechanisms to trastuzumab and introduces mucin 1 (MUC1) as a potential target efficient for overcoming such resistance. MUC1 belongs to the mucin family, playing the oncogenic/mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 159 publications
(255 reference statements)
0
10
0
Order By: Relevance
“…For example, the overexpression of this membrane-bound glycoprotein limits the effectiveness of 5-fluorouracil treatment in patients with pancreatic cancer ( Kalra and Campbell 2009 ), and decreases sensitivity of cisplatin in SCC ( Zhao et al, 2021 ). Mucin 1 plays a key role in trastuzumab resistance in breast cancer ( Hosseinzadeh et al, 2022 ). The high-expression of MUC1 is associated with a poor prognosis for esophageal cancer patients ( Song et al, 2003 ), contributes to SCC metastasis ( Ye et al, 2011 ), and plays a pivotal role in the progression to AC ( Adil Butt et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the overexpression of this membrane-bound glycoprotein limits the effectiveness of 5-fluorouracil treatment in patients with pancreatic cancer ( Kalra and Campbell 2009 ), and decreases sensitivity of cisplatin in SCC ( Zhao et al, 2021 ). Mucin 1 plays a key role in trastuzumab resistance in breast cancer ( Hosseinzadeh et al, 2022 ). The high-expression of MUC1 is associated with a poor prognosis for esophageal cancer patients ( Song et al, 2003 ), contributes to SCC metastasis ( Ye et al, 2011 ), and plays a pivotal role in the progression to AC ( Adil Butt et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Resveratrol triggers a stepwise inhibition cascade involving Src tyrosine kinase and STAT3 proteins. In order to circumvent the problem of trastuzumab resistance in Her2+ patients, scientists have targeted the proto‐oncogene MUC1 , which is a downstream target of STAT3 [98]. 6Br‐6a is a STAT3 inhibitor that decreased cell proliferation, increased apoptosis and reduced plasticity making it a promising target in breast cancer [99].…”
Section: Potential Treatments Targeting Cell‐intrinsic Pathways Media...mentioning
confidence: 99%
“…It has been shown that MUC1 promotes cell growth and the proliferation of cancer by regulating PI3K/AKT, MEK/ERK, p53, nuclear factor-κB, epidermal growth factor receptor, WNT/β-catenin and JNK/TGF-β ( 3 , 11 , 12 ). MUC1 also regulates tumour cell invasion and metastasis by interacting with E-calmodulin and intercellular adhesion molecules ( 13 , 14 ). In addition, MUC1 promotes tumour angiogenesis and accelerates the invasion and metastasis of tumours by stimulating the expression of proangiogenic factors, such as vascular endothelial growth factor ( 4 , 15 ).…”
Section: Distribution Structure and Biological Characteristics Of Muc1mentioning
confidence: 99%